Clima escolar y nivel de desempeño: un estudio de correlación (2016)
The scholar environments are a living net, that constitute a determinant factor in type of coexistence that it is constructed every day inside of a certain educative intencionality, that is the reason some people educate according to the kind of relationship that they generate, producing an effect in the behavior, atttitude and values of the students, and also in their performance level. The following investigation determined the relationship between the scholar environment and the performance level of the sixth grade students of three educative institutions of the South East of the city of Barranquilla, it is of the applied type, cuantitative aproach, with a correlatioal-predictive design, it is no experimental, and it is transversal cut, it was applied in a population of 274 students, from which a sample of 68 students was taken, in which the respective instrument was applied to, and it was taken into account, to the determination of the performance levels, the SABER tests for the fifth gradeapplied in the year of 2015 by ICFES. The obtained data were processed with the SPSS program, which gave as a result a correlation “r” of 0,74421018 between the scolar environment and the performance level of the students of the three educative institutions that were the objective of the study, concluiding tha there is a positive, direct and high relationship bretween this two variables.